Pengaruh Return On Equity dan Debt Equity Ratio Terhadap Price Earning Ratio Pada Sektor Telekomunikasi Yang Terdaftar di BEI - Kasir; Kartika (Jurnal Riset Bisnis dan Investasi, 2021)
The purpose of this study was to determine the effect of ROE and DER on PER in telecommunications sector companies listed on the Indonesia Stock Exchange. The data used are secondary data. The regression model used is Multiple Regression Analysis. The results of this study by t-test show that both Return On Equity and Debt to Equity Ratio has an effect on Price Earning Ratio. The F test (simultaneous) states that the Return On Equity and Debt to Equity Ratio simultaneously affect the Price Earning Ratio. Based on the test results, the coefficient of determination shows that the Return On Equity and Debt to Equity Ratio has a simultaneous effect of 81.4% on the Price Earning Ratio. The remaining 19.6% is influenced by other factors not included in this study, such as company size, sales growth.